Sphinkeeper Procedure for Treating Severe Faecal Incontinence—A Prospective Cohort Study - Christopher Dawoud (MDPI AG, 2021)
(1) Background: The Sphinkeeper implantation for faecal incontinence (FI) is a novel surgical procedure with limited data on its clinical efficacy. Therefore, we aimed to assess the functional outcome following Sphinkeeper surgery in patients with refractory FI. (2) Methods: Between 2018 and 2020, eleven consecutive patients (9 female) with FI met the inclusion criteria and were enrolled for surgery. Functional outcome and quality of life were evaluated by standard questionnaires pre- and post-surgery. Migration of protheses was demonstrated by 3D endoanal ultrasound. The median follow-up time was eight months (range 3–18 months). (3) Results: The median age was 75 years (range 46–89 years) with a median BMI of 27.4 (range 21.2–30.1). The median number of implanted prostheses per intervention was nine (range 9–10). We found no intraoperative or early postoperative complications. After two months, two prostheses in one patient had to be removed due to pain at the perianal skin site. The median St. Mark’s incontinence score decreased significantly from 22 to 13 points (p = 0.008). The SF-12 showed a significant improvement (35.9 versus 46.3) after surgery (p = 0.028). A migration of at least one prosthesis was observed in ten patients (91%). Six (60%) prostheses were found at the same level in another ten patients. (4) Conclusion: Sphinkeeper implantation is a promising surgical technique for patients with severe FI. The complication rate is low, and short-term functional improvement can be achieved even in severe forms of FI. Migration of implants commonly occurs.